(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the characteristics of liver cancer patients treated at the 108 Military Central Hospital in 2024. Subjects and methods: A prospective cross-sectional study was conducted on 185 liver cancer patients treated at the 108 Military Central Hospital from February to August 2024. Results: The mean age in the study was 62.2 ± 11.5 years; the male/female ratio was 19.5/1. Common comorbidities included cirrhosis (29.7%), diabetes mellitus (17.3%), hypertension (13.5%), and cancer of other organs (2.7%). Frequently observed clinical symptoms were right hypochondrial pain (78.9%), fatigue and loss of appetite (49.2%), jaundice (16.2%), collateral circulation (5.4%), edema (3.8%), and ascites (4.3%). Liver cancer associated with HBV accounted for 75.1%, HCV for 3.8%, alcohol for 15.2%, and other or no known causes for 4.3%. Treatment and care outcomes: the average hospital stay was 7.56 ± 4.16 days. Upon discharge, 97.8% of patients showed symptom improvement; nursing care quality was rated as good in 89.2% of cases; and 96.2% of patients were satisfied with the care provided. Conclusion: Liver cancer is a disease usually in middle-aged individuals, with a higher incidence in males compared to females. Hepatitis caused by HBV infection is a prevalent risk factor for the disease. Nursing care has achieved positive outcomes in many aspects, with most patients showing symptom improvement upon discharge and expressing satisfaction. This contributes to enhancing treatment efficacy and quality of life in patients with liver cancer.